Slaying the Dragon of Corruption: Application of Multiple-Streams Framework in Anticorruption Policy Processes in Devolved Systems of Government in Kenya - Justa Mwangi; Wilson Muna (International Review of Public Policy)
Although John Kingdon’s multiple streams (MSF) framework is utilized to explain public policy processes in the US and western countries, little empirical evidence exists of its applicability in Africa. This paper addresses this gap by interrogating agenda setting processes that combat corruption in devolved systems of government in Kenya through the lens of this framework. The paper is the result of an empirical study that involved 126 interviews and two focus group discussions involving nine key stakeholders from the counties of Kiambu and Nairobi City, which are two devolved systems of government in Kenya. The paper examines how the state, business, and civil society are intertwined within the anticorruption agenda setting processes of these two counties. The results illuminate the complex relationships between these actors as they switch roles from being facilitators (enablers) of anticorruption agendas to accomplices of corruption (through convergence of mutual interests) and demonstrate the extent to which MSF theory may be considered appropriate in the analysis of such policymaking processes. The authors present several pathways that MSF’s problem, policy, and political streams may converge to create policy windows to combat corruption, and calls for further studies in this area.